Average rate of change of a function d(t) between t1 and t2 can be calculated by
average rate of change
= (d(t2)-d(t1)) /(t2-t1)
Geometrically, it represents the secant between points (t1, d(t1)), and (t2, d(t2)).
Physically, it represents the total displacement between t1 and t2, divided by the elapsed time, t2-t1.
For the given problem,
t1=2
t2=5
t2-t1=5-2=3 seconds
d(t1)=d(2)=16(2^2) = 64 ft
d(t2)=d(5)=16(5^2) = 400 ft
d(t2)-d(t1) = 400-64 = 336 ft
Average rate of change (of displacement)
= (d(t2)-d(t1)) / (t2-t1)
= (336/3)
= 112 ft / s.